Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Alright, let's work through solving for \( c \) given the equation \( 10b = 5(\sqrt{c} + 2) \).
1. Starting with the given equation:
[tex]\[ 10b = 5(\sqrt{c} + 2) \][/tex]
2. First, isolate \(\sqrt{c}\):
[tex]\[ 10b = 5\sqrt{c} + 10 \][/tex]
Subtract 10 from both sides:
[tex]\[ 10b - 10 = 5\sqrt{c} \][/tex]
3. Next, solve for \(\sqrt{c}\):
Divide both sides by 5:
[tex]\[ \frac{10b - 10}{5} = \sqrt{c} \][/tex]
4. Square both sides to solve for \( c \):
[tex]\[ \left(\frac{10b - 10}{5}\right)^2 = c \][/tex]
Simplify the expression inside the square:
[tex]\[ \frac{10b - 10}{5} = 2b - 2 \][/tex]
Therefore:
[tex]\[ c = (2b - 2)^2 \][/tex]
5. Find the equivalent equation:
Notice in this simplified and new expression, the correct form that matches one of the given options would be:
[tex]\[ c = \left( \frac{10b - 10}{5} \right)^2 \][/tex]
This further simplifies to:
[tex]\[ c = \frac{(10b - 10)^2}{25} \][/tex]
Therefore, the equivalent equation to find \( c \) is:
[tex]\[ c = \frac{(10b - 10)^2}{25} \][/tex]
This matches the provided option:
[tex]\[ c = \frac{(10 b - 10)^2}{25} \][/tex]
So the correct answer is:
[tex]\[ c = \frac{(10 b - 10)^2}{25} \][/tex]
1. Starting with the given equation:
[tex]\[ 10b = 5(\sqrt{c} + 2) \][/tex]
2. First, isolate \(\sqrt{c}\):
[tex]\[ 10b = 5\sqrt{c} + 10 \][/tex]
Subtract 10 from both sides:
[tex]\[ 10b - 10 = 5\sqrt{c} \][/tex]
3. Next, solve for \(\sqrt{c}\):
Divide both sides by 5:
[tex]\[ \frac{10b - 10}{5} = \sqrt{c} \][/tex]
4. Square both sides to solve for \( c \):
[tex]\[ \left(\frac{10b - 10}{5}\right)^2 = c \][/tex]
Simplify the expression inside the square:
[tex]\[ \frac{10b - 10}{5} = 2b - 2 \][/tex]
Therefore:
[tex]\[ c = (2b - 2)^2 \][/tex]
5. Find the equivalent equation:
Notice in this simplified and new expression, the correct form that matches one of the given options would be:
[tex]\[ c = \left( \frac{10b - 10}{5} \right)^2 \][/tex]
This further simplifies to:
[tex]\[ c = \frac{(10b - 10)^2}{25} \][/tex]
Therefore, the equivalent equation to find \( c \) is:
[tex]\[ c = \frac{(10b - 10)^2}{25} \][/tex]
This matches the provided option:
[tex]\[ c = \frac{(10 b - 10)^2}{25} \][/tex]
So the correct answer is:
[tex]\[ c = \frac{(10 b - 10)^2}{25} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.